Pro and Cons Contestation on The Increase of Marriage Age in Indonesia - Supraptiningsih, Umi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The age of marriage enhancement as mandated by Law no. 16 of 2019 is increasing the minimum age for marriage from 16 years for women and 19 years for men to 19 years for both women and men. However, this rule has not been accepted wholeheartedly by the community, so there are pros and cons. This study focuses on answering three questions: 1) Why are there pros and cons in the provisions of Law no. 16 in 2019 within a society? 2) What steps are taken by the community in violating the provisions of Law no. 16 of 2019? 3) What steps have been taken by the KUA and the Religious Courts in implementing the provisions of Law Number 16 of 2019? This research uses qualitative research with discourse analysis method. The researcher uses Pierre Bourdieu's theory to see the dynamics of the pros and cons contestation in increasing the age of marriage. With the genetic structuralism approach, to unite the origins of the individual mental structure, which is the product of the unification of the social structure that surrounds it. There are groups of people who agree to increase the age of marriage, and there are groups against it. The importance of mature marriage is to reduce divorce rates, poverty rates, children dropping out of school, maternal and child mortality rates. On the other hand, some people still prioritize the legal requirements of marriage by fulfilling the provisions of Islamic law (alternative options) not cumulative as required in the conditions for a valid marriage in the UUP. The arguments of people against the increase of marriageable age are based on the background of community culture, economic conditions, and free lifestyle of teenager. Unregistered marriage (nikah siri), legalization of marriage procedure and marriage dispensation are alternative steps taken by people who are against the increase of marriage age. KUA (religious affairs office) and the Religious Courts as the frontline in maintaining the mandate of Law no. 16 of 2019 using legal norms, still tightening the provisions on the age limit for marriage, marriage dispensation and legalization of marriage.